Escola Familia: A proposal - Carani, George; Carani, José; Strong-Wilson, Teresa (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2014)
Alphabetização (literacy) of young children involves a school exclusively devoted to the early years, parental participation, and teachers specialized in early literacy. This is the basis of José Carani’s proposal for an escola familia in the municipality of Cambé (Brazil). This Note from the Field, based on our conversations with José, relates his proposal to the Canadian context.